What Configuration of the Atmospheric Circulation Drives Extreme Net and Total Moisture Transport Into the Arctic - Papritz, Lukas; id_orcid:0 000-0002-2047-9544; Dunn-Sigouin, Etienne (Geophysical Research Letters, 2020)
ISSN:0094-8276 ISSN:1944-8007